AKAD YANG CACAT DALAM HUKUM PERJANJIAN ISLAM - CUT LIKA ALIA (PREMISE LAW JURNAL, 2015)
A contract in Islam can basically be made in action which can cause legal consequence for the parties concerned. However, there are certain contracts which can be revoked because there are some defects which can delete the willingness or desire of another party. The elements of a contract are considered defect when basic principles and requirements of the contract, such as ikrah (coercion), ghalath (error), gabhn (price concealing), tadlis (fraud), jahalah (vagueness), and gharar (bet) are not fulfilled. The legal consequences of a defect contract in the Islamic agreement are as follows: the contract is revoked by law, and it can also be revoked, the contract will be invalid when basic principles and requirements are not fulfilled, while the contract can be revoked when it contains coercion and error. The legal remedy by the losers because of a defect contract is by conducting khiyar (voting rights), reconciliation, or for more transactions, arbitration can be done through Basyarnas in settling the dispute among the parties or through the Religious Court. Keywords: Defect Contract, Islamic Agreement, Settling Dispute